A Nano-Biosensor for the Detection of 185delAG Mutation in BRCA1 Gene, Leading to Breast Cancer. (20th October 2016) - Eftekhari-Sis, Bagher; Karaminejad, Sajede; Karimi, Farrokh
ABSTRACT: A method was developed for the detection of 185delAG mutation in BRCA1 gene, which is responsible for 85% and 63% lifetime risks of hereditary breast and ovarian cancer in women, respectively. The protocol is based on the quenching and recovering fluorescence emission of fluorescein-based dye (FAM)-labeled DNA in the presence of graphene oxide (GO), followed by addition of cDNA or mDNA. In addition, ligase reaction between a DNA probe attached to GO and a DNA possessing FAM on 5′ terminal in the presence of cDNA or mDNA was applied.